1987
DOI: 10.2466/pr0.1987.61.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Attributions Based on Managers' Self-Presentation, Sex, and Weight

Abstract: Attributions based on written accounts of self-presentations by hypothetical managers were studied. Contrary to prior research, college students did not rate managers sharing credit with subordinates less favorably than managers merely disclosing personal obstacles overcome. A critical difference between this study and the prior one seemed to be that performance was portrayed as strictly a team effort, whereas in the prior study the manager made a significant individual contribution. Credit-sharing, male manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…Similar to previous findings (e.g., Decker, 1987; Klassen et al., 1993; Pingitoire et al., 1994; Rothblum et al., 1988), the two studies reported here show that overweight and obese individuals were less likely than were normal‐weight individuals to be hired for a position in sales management or accorded helping behavior if involved in a traffic accident. This is in accordance with the suggestion that overweight and obese individuals are negatively stigmatized, at least in socioeconomically developed settings (Falkner et al., 1999; Kilbourne, 1994; Puhl & Brownell, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to previous findings (e.g., Decker, 1987; Klassen et al., 1993; Pingitoire et al., 1994; Rothblum et al., 1988), the two studies reported here show that overweight and obese individuals were less likely than were normal‐weight individuals to be hired for a position in sales management or accorded helping behavior if involved in a traffic accident. This is in accordance with the suggestion that overweight and obese individuals are negatively stigmatized, at least in socioeconomically developed settings (Falkner et al., 1999; Kilbourne, 1994; Puhl & Brownell, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…For example, Decker (1987) used written descriptions of hypothetical managers. Individuals who were described as average weight were rated as significantly more desirable supervisors, whereas those who were described as overweight were judged more harshly for undesirable behaviors (e.g., taking credit for someone else's work).…”
Section: Occupational Hiringmentioning
confidence: 99%
“…Similarly, studies investigating whether male or female raters are more likely to discriminate against overweight individuals in employment contexts present a mixed picture. For example, Jasper and Klassen () found that only men rated obese female salespeople as less desirable to work with, Decker () found that women judged overweight female managers as less desirable to have as a supervisor than male raters, and McKee and Smouse () did not find a significant difference in how male and female clients rated overweight counselors. These mixed findings preclude any firm conclusions about the relationship between rater sex and weight bias based on a qualitative review of the literature.…”
Section: Hypotheses and Research Questionsmentioning
confidence: 99%
“…Other studies have manipulated descriptive sizes of targets and examined judgments. Decker (1987) asked participants to compare managers who were described as average weight or noticeably overweight . Jasper and Klassen (1990) had participants evaluate an obese or nonobese salesperson (based on body build).…”
mentioning
confidence: 99%